Global return on investment and cost-effectiveness of WHO's HEAR interventions for hearing loss: a modelling study. Issue 1 (January 2022) - Tordrup, David; Smith, Robert; Kamenov, Kaloyan; Bertram, Melanie Y; Green, Nathan; Chadha, Shelly; ,
Summary: Background: To address the growing prevalence of hearing loss, WHO has identified a compendium of key evidence-based ear and hearing care interventions to be included within countries' universal health coverage packages. To assess the cost-effectiveness of these interventions and their budgetary effect for countries, we aimed to analyse the investment required to scale up services from baseline to recommended levels, and the return to society for every US$1 invested in the compendium. Methods: We did a modelling study using the proposed set of WHO interventions (summarised under the acronym HEAR: hearing screening and intervention for newborn babies and infants, pre-school and school-age children, older adults, and adults at higher risk of hearing loss; ear disease prevention and management; access to technologies such as hearing aids, cochlear implants, or hearing assistive technologies; and rehabilitation service provision), which span the life course and include screening and management of hearing loss and related ear diseases, costs and benefits for the national population cohorts of 172 countries. The return on investment was analysed for the period between 2020 and 2030 using three scenarios: a business-as-usual scenario, a progress scenario with a scale-up to 50% of recommended coverage, and an ambitious scenario with scale-up to 90% of recommended coverage. Using data for hearing loss burden from the Global Burden of Disease Study 2019, a transition model with three states (general population, diagnosed, and those who have died) was developed to model the national populations in countries. For the return-on-investment analysis, the monetary value of disability-adjusted life-years (DALYs) averted in addition to productivity gains were compared against the investment required in each scenario. Findings: Scaling up ear and hearing care interventions to 90% requires an overall global investment of US$238·8 billion over 10 years. Over a 10-year period, this investment promises substantial health gains with more than 130 million DALYs averted. These gains translate to a monetary value of more than US$1·3 trillion. In addition, investment in hearing care will result in productivity benefits of more than US$2 trillion at the global level by 2030. Together, these benefits correspond to a return of nearly US$15 for every US$1 invested. Interpretation: This is the first-ever global investment case for integrating ear and hearing care interventions in countries' universal health coverage services. The findings show the economic benefits of investing in this compendium and provide the basis for facilitating the increase of country's health budget for strengthening ear and hearing care services. Funding: None.